Speaker matters: Natural inter-speaker variation affects 4-month-olds' perception of audio-visual speech. Issue 2 (April 2020) - Pejovic, Jovana; Yee, Eiling; Molnar, Monika
In the language development literature, studies often make inferences about infants' speech perception abilities based on their responses to a single speaker. However, there can be significant natural variability across speakers in how speech is produced (i.e., inter-speaker differences). The current study examined whether inter-speaker differences can affect infants' ability to detect a mismatch between the auditory and visual components of vowels. Using an eye-tracker, 4.5-month-old infants were tested on auditory-visual (AV) matching for two vowels (/i/ and /u/). Critically, infants were tested with two speakers who naturally differed in how distinctively they articulated the two vowels within and across the categories. Only infants who watched and listened to the speaker whose visual articulations of the two vowels were most distinct from one another were sensitive to AV mismatch. This speaker also produced a visually more distinct /i/ as compared to the other speaker. This finding suggests that infants are sensitive to the distinctiveness of AV information across speakers, and that when making inferences about infants' perceptual abilities, characteristics of the speaker should be taken into account.